Methodology and results of thermal calculation of one-through steam generators for NPP of small power - Kravchenko, V.P.; Xiaolong Zhou (Вопросы атомной науки и техники, 2020)
Due to the invaluable interest in small-scale nuclear power plants around the world, it has been proposed to pay sufficient attention to the design of appropriate equipment, which can make Ukraine with its great potential as a producer a supplier of such nuclear power plants. The work considers the method of thermal calculation of a oncethrough steam generator with a coil heating surface and superheating of steam. As a result of analysis and comparison of the results, formulas were selected for calculating six different conditions of heat transfer: lumbar flow around the coil package with coolant and five heat transfer sections during the movement of the working fluid in the tube. The results of calculating the heat transfer surface for a steam generator with a capacity of 45 MW are presented. The obtained results correlate well with the calculation data by the ASPEN-TECH computer code. В связи с большим интересом во всем мире к АЭС малой мощности предложено уделять достаточное внимание проектированию соответствующего оборудования, что может сделать Украину с ее мощным потенциалом производителя поставщиком таких АЭС. В работе рассмотрена методика теплового расчета прямоточного парогенератора со змеевиковой поверхностью нагрева и перегревом пара. В результате анализа и сопоставления результатов были выбраны формулы для расчета шести различных условий теплообмена: поперечного обтекания пакета змеевиков теплоносителем и пяти участков теплообмена при движении рабочего тела в трубке. Приведены результаты расчета поверхности теплообмена для парогенератора мощностью 45 МВт. Полученные результаты хорошо коррелируют с данными расчета компьютерным кодом ASPEN-TECH. У зв’язку з великим інтересом у всьому світі до АЕС малої потужності запропоновано приділяти достатню увагу проектуванню відповідного устаткування, що може зробити Україну з її великим потенціалом виробника постачальником таких АЕС. В роботі розглянуто методику теплового розрахунку прямоточного парогенератора зі змієвиковою поверхнею нагріву та перегрівом пара. В результаті аналізу та співставлення результатів було вибрано формули для розрахунку шести різних умов теплообміну: поперекового обтікання пакету змієвиків теплоносієм та п’яти ділянок теплообміну при русі робочого тіла в трубці. Наведено результати розрахунку поверхні теплообміну для парогенератору потужністю 45 МВт. Отримані результати добре корелюються з даними розрахунку комп’ютерним кодом ASPEN-TECH.